Feasibility Analysis of Stem-PjBL Mod El to Build Creativity and Communication Capabilities of Students - Viorita, Nensia; Wahyu, Wawan; Sopandi, Wahyu (FKIP-Universitas Riau, 2022)
This study aims to obtain an appropriate STEM-PjBL learning model in building students' creativity and communication skills. STEM-PjBL is a project learning model that integrates Science, Technology, Engineering, and Math (STEM). In this study using descriptive evaluative research method with 5 research steps. The first is to determine the problem, determine the type of information needed, choose a data collection procedure, choose a procedure for data processing and the last stage is drawing conclusions. The instruments used in this study were the TCOF assessment instrument, validation sheets and student questionnaires. TCOF data was processed and categorized based on the interpretation of Al-Abdali and Al-Balushi scores. The validation data is processed based on the interpretation of Riduwan's score. From the results of the TCOF assessment, the average score obtained is 2.73 which is included in the high level. In the validity test the average score for the creativity of students is 81.2% in the very good category, the communication skills of students are 86.5% in the very good category. Based on the results of the analysis of the 3 assessment instruments, the STEM-PjBL learning model is feasible to be used in improving students' creativity and communication skills.